1989
DOI: 10.1111/j.1432-1033.1989.tb14853.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary structure of twenty three neutral and monosialylated oligosaccharides O‐glycosidically linked to the human secretory immunoglobulin A hinge region determined by a combinationof permethylation analysis and 400‐MHz 1H‐NMR spectroscopy

Abstract: Sialooligosaccharide and asialooligosaccharide alditols, derived from the human milk secretory immunoglobulin A hinge region, have been purified by HPLC using, successively, an amino-bonded silica column and an octadecyl-bonded silica column. Their primary structures were completely resolved by applying a combination of sugar analysis, methylation mass spectrometry and 400-MHz 'H-NMR spectroscopy. In the present report, twenty three oligosaccharide alditols are described and all possess a type two core consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Sensitive analytical procedures have enabled us to identify minor components of the glycan pool in addition to confirming the major glycan structures found by previous investigators (21)(22)(23)(24)(25)(26)(27)(28). The O-glycans on the H chain and the N-glycans on SC presented a wide range of epitopes for adhesin binding.…”
supporting
confidence: 69%
“…Sensitive analytical procedures have enabled us to identify minor components of the glycan pool in addition to confirming the major glycan structures found by previous investigators (21)(22)(23)(24)(25)(26)(27)(28). The O-glycans on the H chain and the N-glycans on SC presented a wide range of epitopes for adhesin binding.…”
supporting
confidence: 69%
“…The 'H NMR chemical shifts (Table 2) (9) and (B) GlcNAc/?l-3Ga&%4GlcNAcB1_6(Ga~l-S)GalNAc-ol (5) tural reporter groups of the constructed tetrasaccharide alditol 4 were similar to those determined by a number of groups for the same structure [23-261. The chemical shifts of larger alditols 5-10 were compared to NMR data of related alditols [24,27,28] and to those of oligo-(N-acetyllactosamino)glycans related to the distal end of the molecules studied [14,29]. The chemical shifts of the GalBl-4GlcNAcBl-6Gal sequence of the hexasaccharide aldito19 were also compared to the spectrum of GaljI14GlcNAc~l-6Gal/7l4GlcNAc (Maaheimo et al, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, both serine and threonine residues are O-glycosylated in the hinge region of serum IgD (17) and secretory IgA1 (18), although in the latter case no experimental data was presented. These differences in O-glycan site occupancy as well as the finding that the O-glycans of secretory IgA1 are larger and more heterogeneous than in myeloma IgA1 (18,19) may reflect tissue-specific glycosylation.…”
mentioning
confidence: 90%
“…The sialylated and neutral glycans identified by NP-HPLC were consistent with earlier reports of the analysis of the desialylated glycan pool (14,16,26,54,55) and confirmed previous findings from this laboratory (14), which indicated that serum IgA1 does not carry the GalNAc neoantigen. The limited repertoire of O-glycan structures attached to serum IgA1, compared with the plasma cells producing IgA1 for mucosal secretion (18,19), indicates tissue-specific O-glycan processing and may reflect the different environments in which these molecules are required to function.…”
Section: Occupancy Of Potential O-glycosylation Sites In the Iga1mentioning
confidence: 99%